2014
DOI: 10.1155/2014/935946
|View full text |Cite
|
Sign up to set email alerts
|

Er:YAG Laser for Brackets Bonding: A SEM Study after Debonding

Abstract: Background. The introduction of Er:YAG laser in dentistry for ablation of hard tissues advocated an alternative method of enamel etching for orthodontics purpose. Materials and Methods. 55 extracted human third molars were inserted in acrylic resin blocks and divided into five groups of 11 teeth. Group 1 was treated with 37% orthophosphoric acid for 30 seconds. Group 2 was treated with laser irradiation (Er:YAG Fidelius III, Fotona, Slovenia) at 80 mJ and 4 Hz. Group 3 underwent laser treatment (80 mJ, 4 Hz), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Studies have reported that 37% phosphoric acid resulted in a greater depth of resin penetration than other etching methods [1]. 37% phosphoric acid concentration with a 30-second application time is the gold standard for enamel etching [19]. Similar findings were reported by Gardner et al in their study, which indicated the use of 37% phosphoric acid with an optimum application time of 30 seconds [4].…”
Section: Discussionsupporting
confidence: 72%
“…Studies have reported that 37% phosphoric acid resulted in a greater depth of resin penetration than other etching methods [1]. 37% phosphoric acid concentration with a 30-second application time is the gold standard for enamel etching [19]. Similar findings were reported by Gardner et al in their study, which indicated the use of 37% phosphoric acid with an optimum application time of 30 seconds [4].…”
Section: Discussionsupporting
confidence: 72%
“…There are different methods for removing composite residuals, like tungsten-carbide burs, Sof-Lex discs, ultrasonic tools, hand instruments, Er:YAG or CO 2 lasers, rubber or composite burs [5][6][7][8] , and many authors have studied those methods to find the one which best combines capability of removing composite residuals, respect for the enamel surface, and operating time. Tungsten carbide burs are faster and more effective than other instruments, and are considered the gold standard 9) ; however, all of these methods cause a certain amount of enamel loss and do not allow restoration of the enamel surface to its original state 9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…This finding was in agreement with several previous studies. 20 , 21 The laser-etched group exhibited clinically acceptable SBSs of 13.59 MPa.…”
Section: Discussionmentioning
confidence: 93%
“…Erbium lasers emit a wavelength of 2.94µm which matches –OH groups in hydroxyapatite 2.8 µm and the main absorption band of water (3 mm). 21 Thus, the irradiation is absorbed strongly by water and increases its affinity for hydroxyl apatite with minimal thermal effect on the pulp. 1 , 3 , 16 In this study, Erbium laser etching was compared to acid etching using 37% phosphoric acid as a control group, since it is the standard and most common etching method.…”
Section: Discussionmentioning
confidence: 99%